Are Face Masks a Problem for Emotion Recognition? Not When the Whole Body Is Visible - Ross, Paddy; George, Emily (Frontiers in Neuroscience, 2022)
The rise of the novel COVID-19 virus has made face masks commonplace items around the globe. Recent research found that face masks significantly impair emotion recognition on isolated faces. However, faces are rarely seen in isolation and the body is also a key cue for emotional portrayal. Here, therefore, we investigated the impact of face masks on emotion recognition when surveying the full body. Stimuli expressing anger, happiness, sadness, and fear were selected from Van den Stock and de Gelder’s (2011) BEAST stimuli set. Masks were added to these images and participants were asked to recognise the emotion and give a confidence level for that decision for both the masked and unmasked stimuli. We found that, contrary to some work viewing faces in isolation, emotion recognition was generally not impaired by face masks when the whole body is present. We did, however, find that when viewing masked faces, only the recognition of happiness significantly decreased when the whole body was present. In contrast to actual performance, confidence levels were found to decline during the Mask condition across all emotional conditions. This research suggests that the impact of masks on emotion recognition may not be as pronounced as previously thought, as long as the whole body is also visible.